Upaya Mengembangkan Kemampuan Mengenal Warna melalui Kegiatan Finger Painting pada Anak Kelompok B di TK Dharma Wanita I Banjarejo Kediri - Leven Yulianti; Ardhana Januar Mahardhani; Muhammad Azam Muttaqin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The ability to identify colors is an important aspect of cognitive development that needs to be developed in early childhood because it impacts children's thinking skills, creativity, and understanding of their surroundings. However, in learning activities, some children still experience difficulties in distinguishing and naming colors due to less engaging learning methods. This study aims to explain the use of finger painting activities as a medium for developing color recognition skills in Group B children at Dharma Wanita I Banjarejo Kindergarten, Plemahan District, Kediri Regency. This study applies a qualitative approach with a descriptive research type. The research subjects included class teachers and children in Group B, while the research object focused on finger painting activities in teaching color recognition. Data collection was carried out through observation, interviews, and document collection. Data analysis used the Miles and Huberman approach which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that finger painting activities can increase children's enthusiasm and participation in the process of learning to recognize colors. Children more quickly understand, name, and distinguish basic colors and mixed colors because they gain direct learning experiences through play and color exploration. In addition, finger painting activities also support the development of creativity, fine motor skills, and children's self-confidence. Therefore, finger painting can be an effective and fun learning tool to enrich the ability to recognize colors for early childhood.